Reformulation of Competition Law Policy From The Perspective of The Implementation of The Green Economy - Sadikin, Nurma Candra Yani; Silalahi, Udin; Sihombing, Jonker (Dinasti Research, 2026)
The necessity to balance economic interests and environmental protection calls for reform in multiple policy frameworks, including legal instruments that regulate business interactions in the market. This research is qualitative in nature, chosen to explore in depth the relationship between competition law and the implementation of a green economy in Indonesia, by analyzing legal documents, regulations, KPPU decisions, academic literature, and best practices in other jurisdictions. The relevant national regulations are the Law on Prohibition of Monopolistic Practices and Unfair Business Competition, in conjunction with Law No. 11 of 2020 on Job Creation, which have not provided regulations that provide legal certainty and are in line with the environmental interests of the green economy. There is an urgent need to reformulate competition law policy to be more adaptive, accompanied by strengthening the role and capacity of the KPPU as an independent institution that conducts competition supervision in a professional, transparent manner, and in line with the sustainable economy agenda. The implementation of Articles 50 and 51 of the Monopoly Practices Law regarding exemptions and state monopolies in strategic sectors needs to be optimized through clearer guidelines so that each exemption remains oriented towards efficiency, sustainability, and the public interest.